Real-Time Digital PWM With Zero Baseband Distortion and Low Switching Frequency - Chierchie, Fernando (2013)
A discrete-time pulse width modulator (PWM) with zero baseband distortion for arbitrary band-limited modulating signals is developed in this paper. It is based on adjusting the duty-cycles of the PWMsuch that the samples of an ideal low-pass filtered version of the PWM signal coincide with the discrete-time samples of the modulating signal. Elaborating on previous approaches in the literature, it is shown that this problem can be stated as a multidimensional inverse function approach, and therefore it can be solved using iterative methods. Starting with the duty-cycle values of a uniform PWM, the successive iterations provide slight duty-cycle corrections that, in the limit, result in zero baseband distortion even for low carrier-to-modulating frequency ratios. Aiming at a practical, real-time implementation two new results are provided. First, explicit bounds on the improvement achievable after each duty-cycle correction are derived. Second, a block processing architecture suitable for real-time implementation is proposed, and the increase of distortion caused by its use is quantified. Several examples with typical band-limited signals demonstrate the performance of the algorithm.